2019
DOI: 10.1159/000495211
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-Conditioned Medium Protects Prefrontal Cortical Neurons from Glutamate-Induced Cell Death by Inhibiting TNF-α Expression

Abstract: Objective: Both excitotoxicity and neurotrophin deficiency may contribute to the etiology of depression and neurodegeneration. Astrocytes not only regulate glutamate metabolism and clearance, they also produce neurotrophins in the brain. However, the direct interaction between neurons and astrocytes remains unknown. Methods: This study evaluated the cellular mechanisms by which astrocyte-conditioned medium (ACM) protects prefrontal cortical neurons from glutamate-induced death by measuring cell viability and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…ACM represents a widely used in vitro model to test the protective effect of astrocyte-released factors on cultured neurons. In particular, it has been shown that ACM can promote the survival and functional recovery of neurons following different types of injury [39][40][41]. Since PEMFs exposure promoted the production of the neuroprotective factor VEGF, we tested the hypothesis that ACM obtained from PEMF-treated 1321N1 cells could protect SH-SY5Y, an extensively used model of neuron cells, from OGD-induced injury.…”
Section: Discussionmentioning
confidence: 99%
“…ACM represents a widely used in vitro model to test the protective effect of astrocyte-released factors on cultured neurons. In particular, it has been shown that ACM can promote the survival and functional recovery of neurons following different types of injury [39][40][41]. Since PEMFs exposure promoted the production of the neuroprotective factor VEGF, we tested the hypothesis that ACM obtained from PEMF-treated 1321N1 cells could protect SH-SY5Y, an extensively used model of neuron cells, from OGD-induced injury.…”
Section: Discussionmentioning
confidence: 99%
“…We prepared an astrocyte-conditioned medium (ACM) based on the protocols of several papers [62][63][64]. C8-D1A cells were cultured in DMEM at 37 • C in a humidified incubator containing 5% CO 2 .…”
Section: Preparation Of Astrocyte-conditioned Medium (Acm)mentioning
confidence: 99%
“…It can cause brain injury by rising the functions of extracellular excitatory amino acids, like glutamate and inhibiting the functions of γ-aminobutyric acid receptors. TNF-α released from reactive astrocytes and activated microglia can promote the release of glutamate [8] and regulate the firing of neurons and seizures. Thus, it is essential to control the severity of neuroinflammation for preventing FS.…”
Section: Introductionmentioning
confidence: 99%